2022
DOI: 10.1177/03635465221107388
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Differences Between the Dominant and Nondominant Legs During a Single-Leg Drop Vertical Jump in Female Soccer Players

Abstract: Background: In soccer, the roles of the dominant (kicking) and nondominant (supporting) legs are different. The kinematic differences between the actions of the dominant and nondominant legs in female soccer players are not clear. Purpose: To clarify the kinematic differences between dominant and nondominant legs during a single-leg drop vertical jump (DVJ) in female soccer players. Study Design: Controlled laboratory study. Methods: A total of 64 female high school and college soccer players were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…The greater vulnerability to ACL injuries of the non-dominant leg of our female players could be explained by the role of the non-dominant leg to stabilise the body and absorb shocks during football-specific activities, and in particular, the kicks or jumps of our fatigue protocol [39]. Interestingly, Nakahira et al [40] showed that during single-leg drop vertical jumps, the knee valgus angle of female footballers at initial contact was greater in the non-dominant compared to the dominant leg. They suggested that these differences might reflect a reduced control of the muscles acting on the knee in the frontal plane due to changes in the contraction patterns of the hamstrings and gastrocnemius muscles acting as knee adductors and abductors of the knee [41].…”
Section: Angle-specific Torquementioning
confidence: 91%
“…The greater vulnerability to ACL injuries of the non-dominant leg of our female players could be explained by the role of the non-dominant leg to stabilise the body and absorb shocks during football-specific activities, and in particular, the kicks or jumps of our fatigue protocol [39]. Interestingly, Nakahira et al [40] showed that during single-leg drop vertical jumps, the knee valgus angle of female footballers at initial contact was greater in the non-dominant compared to the dominant leg. They suggested that these differences might reflect a reduced control of the muscles acting on the knee in the frontal plane due to changes in the contraction patterns of the hamstrings and gastrocnemius muscles acting as knee adductors and abductors of the knee [41].…”
Section: Angle-specific Torquementioning
confidence: 91%
“…Future studies are required to understand the role of gender on patellar instability rates and risk factors. Besides gender, leg dominance has shown to affect the rate of knee injuries in previous studies [11,20]. Though we did not study leg dominance in particular, there were no differences in risk factors between left and right knees (Table 2).…”
Section: Discussionmentioning
confidence: 78%
“…Most reports on ACL injuries and laterality have been related to the dominant leg. It has been reported that female soccer players have a greater knee valgus angle in the non‐dominant leg during the single‐leg vertical jump landing compared to males [15]. In soccer players with ACL non‐contact injuries, a trend for injuries to occur on the dominant (kicking) leg in males and on the non‐dominant (supporting) leg in females was reported [5].…”
Section: Discussionmentioning
confidence: 99%